2021
DOI: 10.3390/ijerph18126301
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of Transitions from Smoking to Electronic Nicotine Delivery System (ENDS) Use: A Daily Diary Investigation

Abstract: Objectives: We aimed to examine patterns in smoking and electronic nicotine delivery system (ENDS) use over an extended period of time (up to 20 weeks) in people who smoked and who had never previously made a successful quit attempt using an ENDS. Design and setting: We conducted a longitudinal mixed-methods study in Dunedin, New Zealand, during 2018 and 2019. Participants: Purposively selected participants (N = 45; age (≥18 years), gender, ethnicities, cigarettes/day) who wished to quit smoking. Interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…Unlike previous research, we found no consistent evidence that vaping may increase the likelihood of later smoking behaviours [14] or act as a cessation pathway from smoking to vaping [2,13]. Instead, in support of Conner et al [18], there are frequent transitions between smoking and vaping and vice versa. This is further supported visually in the Sankey plots exploring behaviours over time.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike previous research, we found no consistent evidence that vaping may increase the likelihood of later smoking behaviours [14] or act as a cessation pathway from smoking to vaping [2,13]. Instead, in support of Conner et al [18], there are frequent transitions between smoking and vaping and vice versa. This is further supported visually in the Sankey plots exploring behaviours over time.…”
Section: Discussioncontrasting
confidence: 99%
“…One possible reason for the conflicting evidence in adults is the high individual variability in smoking and e-cigarette use [18]. Using a daily-diary survey approach to assess smoking and e-cigarette use during an individual's attempt to quit smoking, Conner et al [18] reported that individuals frequently moved between dual usage of both e-cigarettes and cigarettes and exclusive e-cigarette or cigarette use.…”
Section: Is Vaping Increasing or Decreasing Smoking Behaviours?mentioning
confidence: 99%
“…The same factors might have contributed to the comparable effectiveness between ECs and HTPs and to the progressive transition from dual use to solo use by the end of the intervention phase. Dual use is known for being a common transitory state, with transitions to solo use taking variable time to occur [ 38 , 39 ]. In our switching trial, IQOS users reported increased dual use in the first 2 weeks compared to JustFog users, but this quickly stabilized by week 4.…”
Section: Discussionmentioning
confidence: 99%
“…The Center for Tobacco Products requires information to assess the potential impact of a new product on current tobacco user behaviors, including who uses the product, how the product is used, and the effects of its use on the use of other tobacco products. Various study designs can be employed to provide this information, including randomized clinical trials, longitudinal cohort studies, and actual use studies (AUS) [3,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%